The relationship between household’s risk preference and the homeownership decisions among young adults in changing housing market conditions - Le, Vien C. (Kansas State University, 2018)
For many decades, the American Dream of homeownership has been a source of pride and one of the traditional ways to improve financial and non-financial well-being for American households. However, during the recent housing crisis, millions of homeowners lost their homes or experienced negative home equity due to job loss, reductions in work hours, or a decline in home values. The recent housing crisis made many individuals and families rethink their American Dream. As with most investments, there are some risks associated with owning a home, especially when housing markets are volatile and the economy is uncertain. Understanding the relationship between household’s risk preference and homeownership decisions may help households make better and more informed decisions regarding their housing tenure choice. This study investigates the relationship between household’s risk preference and homeownership decisions among young adults made during the stability in the housing market, which occurred around 1993, and during the decline in the housing market, which occurred around 2010. This study also examined demographic and economic characteristics of homeowners during those periods. Two separate datasets from the National Longitudinal Study of Youth 1979 and the National Longitudinal Study of Youth 1997 were utilized to address research questions and research hypotheses under the lens of the expected utility theory. The results showed shifts in household’s rick preferences, homeownership rates, and demographic and economic characteristics between periods. Compared to households who preferred lowest risk level, households who preferred highest risk level were more likely to own a home in both periods. The relationships between household’s risk preference and homeownership decisions did not change between periods. However, some relationships between household’s demographic and economic characteristics and homeownership decisions changed between periods. The findings of this study have several important implications for potential homebuyers, lenders, and personal financial planning practitioners. Household’s risk preference, as well as demographic and economic characteristics, should be considered during the home purchase process. The findings also expand the literature on expected utility theory, household’s risk preference, and homeownership research areas.
Keywords: Risk preference; Risk tolerance; Homeownership; Home ownership; Homeownership decisions; Housing market